Pengembangan Modul Ikatan Kimia dan Bentuk Molekul Berorientasi Nature of Science Untuk Menumbuhkan Literasi Sains Siswa - Nurwanti, Hifzani; Khery, Yusran; Nufida, Baiq Asma (Hydrogen: Jurnal Kependidikan Kimia, 2019)
This development aims to determine the characteristics and feasibility of the o Nature of Science (NOS) oriented module On the Chemical Bonds and Molecular Forms subject material through the 4D stage (Define, design, develop and disseminate). This research and development is carried out up to the stage of development (development) with adjustments based on development needs. The module prototype was validated by 2 expert validator, 1 practitioner validator and 10 students as limited test respondents. Quantitative data were analyzed by percentage formulas and category. Qualitative data in the form of responses and suggestions are used as considerations for revisions. The results of expert validation showed an average percentage of 92.67% with very good categories of material experts, 83.34% with very good categories from product design experts and 76% with good categories from teacher practitioners. The average response of students to the modul prototype is 85.1% with a very good category. This shows that the module that developed is feasible to proceed to a large-scale trial phase.